Yahoo Web Search

  1. Ads
    related to: sec
  1. Triple Sec can be considered a generic and inexpensive version of Cointreau. ... the amount for Cointreau as compared Triple Sec , you should.

    10 Answers · Food & Drink · 24/02/2007

  2. I have lost respect for the SEC due to its extremly weak non-conference scheduling...if you factor beating the cupcakes of the SEC (Miss & Miss St.) thats 6...

    16 Answers · Sports · 31/08/2007

  3. sec ^3(x)dx = ⌠ sec (x) sec ^2(x)dx u=secx du= sec (x)tan(x)dx dv= sec ^2(x)dx v = tan(x) ⌠ sec ^3(x)dx = sec (x...x)- ⌠( sec ^2(x)-1) sec (x)dx ⌠ sec ^3(x)dx = sec (x)tan(x)- ⌠( sec ^2(x) sec (x)dx + ⌠ sec (x)dx transpose ⌠( sec ^2(x) sec (x)dx to...

    3 Answers · Science & Mathematics · 20/03/2011

  4. Since sec θ = 1/cosθ, consider the sign of cosθ (since sec θ and cosθ will have the...cosθ < 0 in Quadrants II and III, sec θ < 0 in Quadrants II and III as...

    1 Answers · Science & Mathematics · 23/08/2011

  5. sec ^2(x) dx multiply and divide with tan x ∫tan x sec ^2(x) dx / tan x let tan x = u sec ^2(x) dx = du now the integral becomes...

    5 Answers · Science & Mathematics · 03/01/2010

  6. I = ∫ sec ^n(x) dx = ∫ sec ^(n-2)(x) sec ^2(x) dx = ∫ sec ^(n-2)(x) dtan(x) = sec ^(n-2)(x) tan(x) - ∫tan(x) (n-2) sec ^(n-2) tan(x) dx = sec ^(n-2)(x) tan(x) - ∫(n-2) sec ^(n-2) tan^2(x) dx = sec ^(n-2...

    3 Answers · Science & Mathematics · 05/02/2011

  7. sec (x) tan^4(x) dx For the integrand tan^4(x) sec (x), use the trigonometric identity tan^2(x) = sec ^2(x)-1... the reduction formula, ∫ sec ^m(x) dx = (sin(x) sec ^(m-1)(x))/(m-1) + (m-2)/(m-1) ∫ sec ^(-2+m)(x) dx, where...

    2 Answers · Science & Mathematics · 25/10/2010

  8. 1.) sec ^ 4 - sec ^ 2 = tan^ 4 + tan^ 2 = sec ^2x( sec ^2x-1) = sec ^2xtan^2x =(1+tan^2x)(tan^2x) =tan^2x+tan^4x answer// 2.) (tan(a...sin^2(a)cos^2(a) ......1..............1 =------------- - ------------- ....cos^2a......sin^2(a) = sec ^2(a)-csc^2(a) answer//

    3 Answers · Science & Mathematics · 21/03/2009

  9. sec (x) * dx => sec (x) * ( sec (x) + tan(x)) * dx / ( sec (x) + tan(x)) => ( sec (x)^2 * dx + sec (x) * tan(x) * dx) / ( sec (x) + tan(x)) u = sec (x) + tan(x) du = sec (x) * tan(x) * dx + sec (x)^2 * dx du / u ...

    4 Answers · Science & Mathematics · 17/04/2013

  10. Hello, ∫ tan²θ sec θ dθ = let's start replacing tan²θ with sec²θ - 1...dθ - ∫ sec θ dθ summing up, we have: ∫ tan²θ sec θ dθ = ∫ sec θ sec²θ dθ - ∫ sec θ dθ let's integrate ∫ sec θ sec²θ d...

    1 Answers · Science & Mathematics · 10/05/2011

  1. Ads
    related to: sec
  1. Try asking your question on Yahoo Answers